7 - ‘Adversely Incorporated yet Moving up the Social Ladder?’: Labour Migrants Shifting the Gaze from Agricultural Investment Chains to ‘Care Chains’ in Capitalist Social Reproduction in Senegal - Dieng, Rama Salla (Africa Development, 2022)
In Senegal, the growth of horticulture has been particularly rapid in the last decade or so, partly coinciding with the 2007–2008 ‘land rush’ and a boom in agricultural investment. This article analyses the implications of the rise in foreign direct investment (FDI) in the horticultural sector in northern Senegal. Specifically, it examines FDI’s effects on labour migration and the social reproduction of rural classes of labour through an intersectional feminist and gendered lens. It argues that invisibilised ‘care chains’ that overly burden women, and communities of solidarities, play a crucial role in the social reproduction of horticultural workers, most specifically migrant workers, and provide a subsidy to agrarian capital. Yet, capitalist development does not always translate to better wages and more inclusive laws and policies for horticultural wage workers and providers of caring labour who are adversely incorporated in these political economies. As a result, this requires further attention from policy-makers and political leaders. Using a combination of working-life histories and survey data gathered through two rounds of fieldwork over two years, and secondary data from relevant databases, this article focuses on the River Valley Region and Louga to analyse the emerging challenges of labour migration, social reproduction and caring labour in rural Senegal.